2019
DOI: 10.20463/jenb.2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training at lactate threshold and detraining for 12 weeks on body composition, aerobic performance, and stress related variables in obese women

Abstract: [Purpose]The purpose of this study was to investigate the effect of diet plus exercise training and detraining for 12 weeks on body composition, aerobic performance, and stress-related variables in obese women.[Methods]Twenty-five women in their 20s-40s with 30% body fat and body mass indices above 25 kg/m2 were divided into HRLT (heart rate at lactate threshold) and HRLT + 5% groups. Dietary intervention of 70% recommended dietary allowance (RDA) and exercise treatment composed of aerobic exercises on a bicyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The decrease in dietary intake and the increase in daily activity are thought to be caused by motivation of body weight reduction and health care via participating in the study. 23 These changes appears to have resulted in body composition and aerobic improvement in the CON group without exercise intervention. However, given the purpose of the study, and because there was no significant difference in dietary intake and daily activity at each time point, we concluded that the difference between the two groups of dependent variables (body composition, aerobic performance, and ANS function) was not affected by dietary intake and daily activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The decrease in dietary intake and the increase in daily activity are thought to be caused by motivation of body weight reduction and health care via participating in the study. 23 These changes appears to have resulted in body composition and aerobic improvement in the CON group without exercise intervention. However, given the purpose of the study, and because there was no significant difference in dietary intake and daily activity at each time point, we concluded that the difference between the two groups of dependent variables (body composition, aerobic performance, and ANS function) was not affected by dietary intake and daily activity.…”
Section: Discussionmentioning
confidence: 97%
“…Park et al 23 verified that a dietary intervention of 70% of recommended dietary allowance and exercise training corresponding to the heart rate at the LT for 12 weeks effectively improved body composition, aerobic performance, and stress. These findings show that moderate aerobic exercise can improve ANS function and prevent and treat obesity.…”
mentioning
confidence: 99%
“…Data from the remaining four subjects were discarded due to withdrawal ( n = 4). The required sample size was estimated using an effect size (ES = 0.49) reported in the effect of exercise on cardiopulmonary fitness [ 22 ]. With an alpha of 0.05 and the desired power of 0.80, the total sample size necessary to achieve statistical significance was estimated to be 12 participants.…”
Section: Methodsmentioning
confidence: 99%
“…After approximately 10 min of rest, four pads were placed on the wrists and ankles using an HRV meter (LAXTHA; CANS-3000, Daejeon, Republic of Korea), and participants' HRV was measured in the resting condition. The following parameters were evaluated: standard deviation (SD) of successive differences (SDNN) and root mean square of successive differences (RMSSD) for the time domain methods and low frequency (LF) band, high frequency (HF) band, and LH/HF band ratio for the frequency domain methods [33]. All athletes performed the following in 90-min sessions: Warm-up, interval training, and cool-down.…”
Section: Ans Functionmentioning
confidence: 99%